Hydrophobic white carbon black and its preparation method and application
By using raw materials such as vinyl trialkoxysilane and 1,1,1,3,5,5-heptamethyltrisiloxane on white carbon black, the problem of strong hydrophilicity of white carbon black is solved, and its hydrophobicity is greatly improved and acid-base maintenance is maintained, and its industrial application field is expanded.
Patent Information
- Application Number
- CN202411747159.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Due to the existence of silicon hydroxyl groups, the existing white carbon black has strong hydrophilicity, which limits its penetration and dispersion ability in organic systems and affects its wide application in the industrial field.
Vinyl trialkoxysilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane were mixed evenly, Pt catalyst was added, and the reaction was carried out through a micro-channel reactor to form a hydrophobic agent, and mixed with white carbon black and heated and stirred to remove low boiling substances to obtain hydrophobic white carbon black.
This method does not change the acidity and alkalinity of white carbon black, significantly improves its hydrophobicity and broadens its application scope in rubber, plastic, coatings, inks and other fields.
Smart Images

Figure CN119192879B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to hydrophobic white carbon black and a preparation method and application thereof. Background Art
[0002] The production process of fumed silica often involves the chemical reaction of silicon tetrachloride or methyltrichlorosilane in a high-temperature hydrogen-oxygen flame, which is generated through hydrolysis and polycondensation. In this process, due to the incompleteness of the polycondensation reaction, a large number of silanol groups will be retained inside the silicon particles and their aggregates. In contrast, silica prepared by precipitation is obtained by the reaction of sodium silicate with sulfuric acid, followed by a series of physical treatments (such as washing, precipitation, and drying). Its surface characteristics are also significantly rich in silanol groups.
[0003] The presence of silanol groups endows silica with hydrophilic and oil-repellent properties, which significantly hinders its penetration and dispersion capabilities in organic systems, thereby limiting the potential for widespread application of fumed silica in multiple industrial fields.
[0004] The current surface modification strategy of silica mainly focuses on using silicone oil, silazane or chlorosilane as hydrophobic modifiers and treating them under high temperature conditions. Silicone oil treatment works through a surface adsorption mechanism, but the effect is limited by the free state of some polysiloxanes; silazane treatment can effectively remove hydroxyl groups and give silica alkaline characteristics; chlorosilane treatment causes the surface of silica to be acidic. Among these methods, the introduction of Si-CH3 groups plays a key role in achieving the hydrophobic transformation of silica. Acidic or alkaline modified silica will affect the mechanical properties of the material when mixed with polymer materials (such as rubber, plastic, etc.). For example, in silicone rubber, if the pH value of silica is too low or too high, it will cause the cleavage of the silicone rubber molecular chain, thereby reducing the mechanical properties and service life of the material. In the production process of rubber products, if the pH value of silica is not suitable, it will also affect the mixing processing of the rubber.
[0005] However, in view of the increasing demand for the application of silica in various fields, the development of a preparation technology that can significantly improve its hydrophobicity while maintaining or not affecting its original acidity and alkalinity has become an important direction of current research. Such a technological breakthrough will help broaden the application scope of fumed silica and meet a wider range of market needs. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a hydrophobic silica, wherein the prepared hydrophobic agent reacts with silica without changing the acidity and alkalinity of silica and improves the hydrophobicity.
[0007] The invention also provides a preparation method thereof, which is simple and feasible and suitable for large-scale production.
[0008] The invention also provides application of the invention, which is used as a silicone rubber reinforcing agent.
[0009] The method for preparing the hydrophobic silica of the present invention comprises the following steps:
[0010] (1) Vinyltrialkoxysilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane are uniformly mixed, a Pt catalyst is added to obtain a reaction solution, the reaction solution is introduced into a microchannel reactor, heated for reaction, and then introduced into a reactor for further stirring and reaction. After the reaction is completed, unreacted components are removed;
[0011] (2) The hydrophobic agent is obtained by distillation, and the bottom of the kettle is recycled as a catalyst;
[0012] (3) Mix the silica and the hydrophobic agent evenly, heat and stir them, remove low-boiling substances, and obtain hydrophobic silica.
[0013] The hydrophobic agent has a structure as shown in Formula I:
[0014]
[0015] Formula I;
[0016] Wherein R is methyl or ethyl.
[0017] The reaction mechanism of the hydrophobic agent of the present invention is as follows Figure 1 As shown, the reaction mechanism of hydrophobic agent treatment of silica is as follows Figure 2 shown.
[0018] The vinyltrialkoxysilane in step (1) is one of vinyltrimethoxysilane and vinyltriethoxysilane, and the mixing ratio of vinyltrialkoxysilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane is in a molar ratio of (1.02-1.2):1.
[0019] The Pt catalyst in step (1) can be a Karstedt catalyst, a Speier catalyst, chloroplatinic acid or the bottoms in step (2), and the amount used is 2 to 20 ppm based on Pt. The bottoms in step (2) are preferably used as a catalyst for recycling.
[0020] The process of uniformly mixing the white carbon black and the hydrophobic agent in step (3) is carried out under the protection of nitrogen or inert gas.
[0021] The inert gas is argon or helium.
[0022] The amount of the hydrophobic agent used in step (3) is 3% to 15% of the mass of the white carbon black.
[0023] The white carbon black in step (3) is hydrophilic fumed white carbon black or hydrophilic precipitated white carbon black, and the surface area is 100-380m2 / g;
[0024] The reaction temperature of the heating reaction in step (1) is controlled by the microchannel reactor at 90-130°C. The reaction time of the reaction liquid in the microchannel is 2-10 minutes, and then the reaction liquid enters the reactor to continue the heat preservation and stirring reaction time for 1-2 hours.
[0025] The heat transfer oil device of the microchannel reaction equipment described in step (1) is connected to the heating heat transfer oil pipeline of the reactor, and the reaction heat is used to maintain the temperature of the reactor to continue the reaction.
[0026] The stirring treatment temperature in step (3) is 200-300° C., and the treatment time is 2-6 hours.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The raw materials used in the synthesis of the hydrophobic agent of the present invention are common raw materials, which have all been industrialized and produced. The raw materials are easy to obtain, the cost is low, the catalyst can be used repeatedly, the reaction is safer, and the catalyst is not contained by distillation treatment, which has no effect on various subsequent applications. At the same time, there are multiple alkoxy groups with good reaction activity and trimethylsilyl groups rich in lipophilicity. The alkoxy group can be effectively reacted and grafted with the surface of white carbon black, and the grafting is stable. The trimethylsilyl group provides excellent hydrophobicity. The hydrosilylation reaction has a faster reaction speed and is accompanied by violent heat release during the reaction process. Under the traditional single-pot reaction conditions, there is a greater safety risk, and the product by-products obtained are many. The reaction is carried out using a microchannel reactor. Due to the limited liquid inventory in the reactor channel, the reaction can be effectively induced under higher temperature conditions, and the temperature can be accurately controlled. This characteristic makes it possible for most of the hydrosilylation reactions to be completed in the microchannel reactor, thereby effectively avoiding the concentrated release of heat during the reaction process, thereby reducing the potential danger. In addition, the heat released by the silane addition reaction in the microchannel reactor can be effectively utilized in the subsequent heating process of the reactor to continue to provide the required temperature conditions for the reaction. The combined use of the microchannel reactor and the reactor can improve the reaction efficiency while ensuring the complete reaction. This method not only improves the reaction efficiency, but also achieves the goal of green and energy-saving production. 4. The hydrophobic silica prepared by the present invention has strong permeability and is more thoroughly treated with hydroxyl groups because the hydrophobic agent is a small molecule substance. Due to its structural characteristics, the hydrophobic silica obtained by the treatment is equivalent to grafting a molecular structure containing a large amount of silicon methyl groups with a certain degree of freedom on the surface of the silica. The hydrophobic silica has excellent compatibility with various organic polymers.
[0029] 5. The hydrophobic agent prepared by the present invention reacts with white carbon black without changing the acidity and alkalinity of white carbon black, and improves the hydrophobicity, thereby broadening its application fields, such as rubber, plastics, coatings, inks and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is the reaction mechanism diagram of the hydrophobic agent of the present invention;
[0031] Figure 2 The figure is a reaction mechanism diagram of treating white carbon black with a hydrophobic agent according to the present invention;
[0032] Figure 3 is the hydrogen nuclear magnetic resonance spectrum of Example 1;
[0033] Figure 4 is the hydrogen nuclear magnetic resonance spectrum of Example 2;
[0034] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of Example 3. DETAILED DESCRIPTION
[0035] The present invention will be further described below with reference to the embodiments.
[0036] Unless otherwise specified, all raw materials used in the examples are commercially available.
[0037] Example 1
[0038] The preparation of the hydrophobic agent comprises the following steps:
[0039] (1) Vinyl trimethoxysilane and 1,1,1,3,5,5,5-heptamethyl trisiloxane were mixed uniformly in a molar ratio of 1.02:1, and Karstedt catalyst was added in an amount of 2 ppm based on Pt. The mixture entered a microchannel reactor, and the microchannel was kept at a stable temperature of 130°C. The reaction liquid was retained in the microchannel for 2 minutes. The mixture entered a reactor, and the reaction heat in the microchannel reactor was used to heat the reactor. The temperature in the reactor was controlled at 130°C. The reaction was continued for 2 hours, and the unreacted components were removed.
[0040] (2) Distillation is performed to obtain hydrophobic agent A and the bottom of the kettle. The hydrogen nuclear magnetic resonance spectrum of the hydrophobic agent is shown in Figure 3 shown.
[0041] The product NMR hydrogen spectrum and mass spectrum test data are as follows:
[0042] 1H NMR (CDCl3, 400 MHz): δ 3.60-3.51 (m, 9.00H), 1.08 (d, J = 7.6 Hz,0.36H), 0.71-0.46 (m, 3.74H), 0.18-0.02 (m, 21.91H); GCMS (EI): Calcd forC 11 H 31 O5Si4[M-Me]+ 355.12, Found: 355.20.
[0043] Example 2
[0044] The preparation of the hydrophobic agent comprises the following steps:
[0045] (1) Vinyl triethoxysilane and 1,1,1,3,5,5,5-heptamethyl trisiloxane were mixed uniformly in a molar ratio of 1.2:1, and the bottom of the kettle in Example 1 was added as a catalyst, with an addition amount of 20 ppm in terms of Pt, and the mixture was introduced into a microchannel reactor. The microchannel was kept stable at 90°C, and the retention time of the reaction liquid in the microchannel was 10 min. The mixture was introduced into a reactor, and the reaction heat in the microchannel reactor was used to heat the reactor. The temperature in the reactor was controlled to be 90°C, and the reaction was carried out for 1 h to remove unreacted components.
[0046] (2) Distillation is performed to obtain hydrophobic agent B and the bottom of the kettle. The hydrogen nuclear magnetic resonance spectrum of the hydrophobic agent is shown in Figure 4 shown.
[0047] The product NMR hydrogen spectrum and mass spectrum test data are as follows:
[0048] 1 H NMR (CDCl3, 400 MHz): δ 3.84 (q, J = 7.0 Hz, 6.00H), 1.25 (t, J =7.0 Hz, 9.09H), 1.08 (d, J = 7.6 Hz, 0.46H), 0.69-0.38 (m, 3.53H), 0.14-0.02(m, 20.57H); GCMS (EI): Calcd for C 14 H 37 O5Si4[M-Me]+ 397.17, Found: 397.20.
[0049] Example 3
[0050] The preparation of the hydrophobic agent comprises the following steps:
[0051] (1) Vinyltrimethoxysilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane were mixed uniformly in a molar ratio of 1.1:1, and the bottom of the kettle in Example 2 was added as a catalyst, with an addition amount of 15 ppm in terms of Pt, and then the mixture was introduced into a microchannel reactor. The microchannel was kept stable at 100° C. The retention time of the reaction liquid in the microchannel was 8 min, and then the mixture was introduced into a reactor. The reaction heat in the microchannel reactor was used to heat the reactor. The temperature in the reactor was controlled to be 100° C. The reaction was carried out for 1.5 h, and the unreacted components were removed.
[0052] (2) Distillation yields hydrophobic agent C and the bottoms of the kettle. The hydrogen nuclear magnetic resonance spectrum of the hydrophobic agent is as follows: Figure 5 shown.
[0053] The product NMR hydrogen spectrum and mass spectrum test data are as follows:
[0054] 1 H NMR (CDCl3, 400 MHz): δ 3.60-3.51 (m, 9.00H), 1.08 (d, J = 7.6 Hz,0.36H), 0.71-0.46 (m, 3.74H), 0.18-0.02 (m, 21.91H); GCMS (EI): Calcd forC 11 H 31 O5Si4[M-Me]+ 355.12, Found: 355.20.
[0055] Example 4
[0056] The hydrophobic agent A obtained in Example 1 was added in a nitrogen atmosphere with a specific surface area of 100 m 2 / g of precipitated hydrophilic silica ①, the amount of hydrophobic agent used is 3% of the amount of silica, and the stirring treatment time is 6h at 200℃ to obtain hydrophobic silica 1.
[0057] Example 5
[0058] The hydrophobic agent B obtained in Example 2 was added in an argon atmosphere, and the specific surface area was 200m 2 / g of fumed hydrophilic silica ②, the amount of hydrophobic agent used is 10% of the amount of silica, at 250°C, the stirring treatment time is 4h, and hydrophobic silica 2 is obtained.
[0059] Example 6
[0060] The hydrophobic agent C obtained in Example 3 was added in a helium atmosphere, and the specific surface area was 380 m 2 / g of fumed hydrophilic silica ③, the amount of hydrophobic agent used is 15% of the amount of silica, and the stirring treatment time is 2h at 300°C to obtain hydrophobic silica 3.
[0061] The treated and untreated white carbon black in the above examples were used as raw materials to prepare rubber compounds. Information on other raw materials used is shown in Tables 1 and 2 below.
[0062] Table 1: Raw rubber raw material information table
[0063]
[0064] Table 2: Hydroxy silicone oil raw material information
[0065]
[0066] Formula process:
[0067] Comparative test of white carbon black ① and white carbon black 1:
[0068] White carbon black ① formula: 110-8s: 650g, 110-1s: 120g, 110-7sk: 30g, white carbon black ①: 360g, hydroxy silicone oil: 28g, zinc stearate: 1.3g.
[0069] White carbon black 1: 110-8s: 650g, 110-1s: 120g, 110-7sk: 30g, white carbon black 1: 360g, hydroxy silicone oil: 22g, zinc stearate: 1.3g.
[0070] Comparative test of white carbon black ② and white carbon black 2:
[0071] White carbon black ②: 110-8s: 650g, 110-1s: 120g, 110-7sk: 30g, white carbon black ②: 360g, hydroxy silicone oil: 40g, zinc stearate: 1.3g.
[0072] White carbon black 2: 110-8s: 650g, 110-1s: 120g, 110-7sk: 30g, white carbon black 2: 360g, hydroxy silicone oil:
[0073] 32g, zinc stearate: 1.3g.
[0074] Comparative test of white carbon black ③ and white carbon black 3:
[0075] White carbon black ③: 110-8s: 650g, 110-1s: 120g, 110-7sk: 30g, white carbon black ③: 360g, hydroxy silicone oil: 50g, zinc stearate: 1.3g.
[0076] White carbon black 3: 110-8s: 650g, 110-1s: 120g, 110-7sk: 30g, white carbon black 3: 360g, hydroxy silicone oil: 43g, zinc stearate: 1.3g.
[0077] Rubber mixing process: Add all the raw rubber, 150g of white carbon black, hydroxy silicone oil and zinc stearate into a kneader and knead into a mass. Then add the remaining white carbon black in 5 times. After all the white carbon black is added, knead evenly and mix at 150℃ for 2h to obtain the mixed rubber.
[0078] The mixed rubber is vulcanized to prepare silicone rubber, and the vulcanization process is as follows:
[0079] Take 70g of the mixed rubber, add 1wt% of the premixed rubber of bis(2,5-dimethylhexane) and polydimethylsiloxane with a molecular weight of 600,000-700,000 in a mass ratio of 1:1, and vulcanize at 170℃×6.5min on a flat vulcanizer to obtain silicone rubber. The obtained silicone rubber was subjected to mechanical property tests, wherein: Structural condition: 7d plasticity value growth rate was tested by GBT12828-2006, determination of plasticity value and recovery value of raw rubber and unvulcanized mixed rubber, and parallel plate method; the tensile strength was tested by GB / T528-2009, determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber; the elongation at break was tested by GB / T528-2009, determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber; the tear strength was tested by GB / T529-2008, determination of tear strength of vulcanized rubber or thermoplastic rubber; the hardness was tested by GB / T6031-2017, determination of hardness of vulcanized rubber or thermoplastic rubber.
[0080] The results are shown in Table 3 below:
[0081] Table 3: Silicone rubber mechanical properties test
[0082]
[0083] From the above comparison, it can be seen that the hydrophobic silica prepared by the present invention as a part of the reinforcing agent shows advantages in mechanical properties and is generally better than the silicone rubber prepared by the traditional process.
[0084] Structured Situation Assessment:
[0085] The mixed rubber was stored at room temperature, and samples were taken at the initial stage, 1d, 3d, and 7d after production to test the plasticity value. The results are shown in Table 4 below:
[0086] Table 4: Plasticity value test results
[0087]
[0088] Through the above comparison, the plasticity value of the rubber compound prepared by using the hydrophobic silica prepared by the present invention increases slowly, thereby it can be determined that the rubber compound has better anti-structural performance and shelf life.
[0089] The carbon content of treated and untreated white carbon black in the above embodiment was tested using the GB / T20020-2013 fumed silica test method. The results are shown in Table 5 below:
[0090] Table 5: Carbon content test results
[0091]
[0092] The results show that the modifier has a high grafting rate on the surface of silica and good reactivity.
[0093] pH test: Take 5g of sample and disperse it in 100g of anhydrous ethanol, stir evenly, add 100g of water and mix evenly, and test the pH value.
[0094] Thickening effect evaluation: 10g of sample was dispersed in 100g of dimethyl silicone oil with a viscosity of 350mPa·s, stirred for 10min, and the fluidity was visually observed. The performance evaluation results are shown in Table 6 below:
[0095] Table 6: Performance evaluation results
[0096]
[0097] Through the above comparison, the pH value of the hydrophobically modified silica of the present invention does not change. At the same time, the hydrophobic silica prepared by the present invention has good fluidity after being mixed with dimethyl silicone oil, indicating that the silica is well modified.
Claims
1. A method for preparing hydrophobic silica, characterized in that: The following steps are involved: (1) Vinyltrialkoxysilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane are uniformly mixed, a Pt catalyst is added to obtain a reaction solution, the reaction solution is introduced into a microchannel reactor, heated for reaction, and then introduced into a reactor to continue the reaction by heat preservation and stirring. After the reaction is completed, unreacted components are removed; (2) The hydrophobic agent is obtained by distillation, and the bottom of the kettle is recycled as a catalyst; (3) Mix the white carbon black and the hydrophobic agent evenly, heat and stir them, remove low-boiling substances, and obtain hydrophobic white carbon black; The reaction temperature of the heating reaction in step (1) is controlled by the microchannel reactor at 90-130°C. The reaction time of the reaction liquid in the microchannel is 2-10 minutes. The reaction liquid then enters the reactor and continues to stir and keep warm for 1-2 hours. The reaction heat in the microchannel reactor is used to heat the reactor. The stirring treatment temperature in step (3) is 200-300° C., and the treatment time is 2-6 hours.
2. The method for preparing hydrophobic silica according to claim 1, characterized in that: The vinyltrialkoxysilane in step (1) is one of vinyltrimethoxysilane and vinyltriethoxysilane, and the mixing ratio of vinyltrialkoxysilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane is in a molar ratio of (1.02-1.2):
1.
3. The method for preparing hydrophobic silica according to claim 1, characterized in that: The Pt catalyst in step (1) is a Karstedt catalyst, a Speier catalyst, chloroplatinic acid or the bottoms in step (2), and the amount used is 2-20 ppm based on Pt.
4. The method for preparing hydrophobic silica according to claim 1, characterized in that: The process of uniformly mixing the white carbon black and the hydrophobic agent in step (3) is carried out under the protection of nitrogen or inert gas.
5. The method for preparing hydrophobic silica according to claim 1, characterized in that: The amount of the hydrophobic agent in step (3) is 3-15% of the mass of the white carbon black.
6. The method for preparing hydrophobic silica according to claim 1, characterized in that: The white carbon black in step (3) is hydrophilic fumed white carbon black or hydrophilic precipitated white carbon black, and the surface area is 100-380m 2 / g.
7. A hydrophobic white carbon black, characterized in that: The method is prepared by any one of claims 1 to 6.
8. An application of the hydrophobic silica according to claim 7, characterized in that: Used as a silicone rubber reinforcing agent.
Citation Information
Patent Citations
Hydrophobic-surface treatment agent and preparation method thereof
CN103224511A
Preparation method of reactive hydrophobic white carbon black
CN118667358A